Project management : a strategic managerial approach / Jack R Meredith; Scott M Shafer - Meredith, Jack R.
"Growth and new developments in project management continue to accelerate in our society, in practice, and in our research publications. Beyond the attention previously (and still) paid to project management, program management, project portfolios, project maturity, project management offices (PMOs), Agile, and other such project issues, we are now seeing attention also directed to billion-dollar "mega-projects",